STUDENTS’ ATTITUDE TOWARD THE IMPLEMENTATION OF ROLE-PLAYING ACTIVITY IN ENGLISH FOR BUSINESS CLASS AT MANAGEMENT DEPARTMENT - Fuad Abdul Baqi (Universitas Bina Bangsa, 2021)
This research is about the students’ attitude toward the implementation of role-playing activities in English for business class of Management Department. English for Business is a compulsory subject for Management Department at Bina Bangsa University. The aim of this research was to describe students' attitudes towards the implementation of role-playing activities in the classroom. Role-playing activities is a very effective and powerful technique that can help students enhance their creativity and ability at speaking, it can create a favorable learning environment as well, and classes became more interactive and student-oriented. 40 students of the management study program who took English for Business subject took a part in this research. Data were collected through questionnaires, interviews and observations which were then analyzed and tabulated. The results of this study showed that 80% of students had a positive attitude towards role playing activities during learning process. Recognizing their role in certain situations based on the topics studied in the class and playing the role made them easier to practice speaking English and enhance their English ability. Students were enthusiastic as well to learn English because it was fun for them. students are contented with their performance in role-playing activities